Role of AFB culture, histopathology and laparoscopy in female genital tuberculosis as a cause for chronic pelvic pain - Sharma, Hemlata; Sharma, Saurabh; Bharadwaj, Neelam; Lamba, Indira (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: As Female genital tuberculosis is an important cause of significant morbidity presenting mainly as infertility and chronic pelvic pain so the study was proposed to estimate the prevalence of genital tuberculosis in women with idiopathic chronic pelvic pain by AFB culture, histopathology and laparoscopy. Methods: In this prospective study, we enrolled 65 women with idiopathic chronic pelvic pain. Diagnostic laparoscopy was done and Endometrial biopsy or menstrual blood was taken and sent for AFB culture and histopathological examination. Results: In this study, the prevalence of genital TB in women with CPP was 35.38% (24/65) of which23 had gross findings of genital TB and one had pelvic congestion with positive result in AFB culture. Laparoscopic findings were normal in 13 out of 65 women (20%) whereas these were abnormal in 52 women. Histological evidence of genital TB was reported in 12.5% (3/24) women. AFB culture reported positive in 16.66% (4/24) women. Conclusions: Genital tuberculosis is an important cause for idiopathic chronic pelvic pain mainly in developing countries. AFB culture of menstrual blood is a simple, noninvasive test that is useful many times especially in unmarried girls or those who are not willing for invasive tests. Laparoscopy is an excellent tool in diagnosis of genital TB as it allows direct visualization.